Daniel Barenboim conducts Verdi, Wagner, Haddad, and Czernowin West-Eastern Divan Orchestra - Verdi, Giuseppe 1813-1901; Haddad, Saed 1972-; Verdi, Giuseppe 1813-1901; Verdi, Giuseppe 1813-1901; Verdi, Giuseppe 1813-1901; Czernowin, Chaya; Wagner, Richard 1813-1883; Wagner, Richard 1813-1883; Wagner, Richard 1813-1883 (UNITEL, 2013)
" ... A milestone, not just for the composers and the musicians, but for the Lucerne Festival itself"! That was how Deutschlandradio described this landmark 2013 concert program featuring Daniel Barenboim and the West-Eastern Divan Orchestra's celebration of the 200th birthdays of two giants of 19th century opera, Verdi and Wagner. A glittering selection of overtures and preludes from some of their most legendary operas (Sicilian Vespers, La Traviata, Parsifal, Die Meistersinger von Nürnberg ...) share the program with two contemporary works specially commissioned by the Lucerne Festival for this performance: Que la lumière soit, Jordanian-born Saed Haddad's meditation on efforts to eradicate ignorance, and At the Fringe of our Gaze, his Israeli colleague Chaya Czernowin's musical exploration of how the unknown can be made familiar to differing cultural and religious worlds
Keywords: Overtures; Orchestral music; Operas; Operas -- Excerpts; concert; Preludes (Music); Filmed performances; Dramatic music; Art music; Internet videos